2019
DOI: 10.21203/rs.2.18562/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Asiatic acid attenuates hypertrophic and fibrotic differentiation of articular chondrocytes via AMPK/PI3K/AKT signaling pathway

Abstract: Background Osteoarthritis (OA), the most common joint disorder, is characterized by a progressive degradation of articular cartilage. Increasing evidence suggests that OA is closely associated with cartilage pathologies including chondrocyte hypertrophy and fibrosis.Methods In this study, we showed that Asiatic acid (AA) treatment reduced chondrocyte hypertrophy and fibrosis. First, the cytotoxicity of AA (0, 5, 10, and 20 μM) to chondrocytes was evaluated, and 5 μM was selected for subsequent experiments. The… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Well documented biomarkers of hypertrophy chondrocyte are type X Collagen ( COL X ), matrix metalloproteinase ( MMP‐13 ) genes, Runt domain transcription factor 2 ( RUNX2 ) and Cyclooxygenase‐2 ( COX‐2 ) are linked to chondrocyte hypertrophy as well (Frischholz, Berberich, Böck, Meffert, & Blunk, 2020; N. Liu et al., 2020; Yahara et al., 2016). The chondrocytes were treated with COL I scaffolds and dSCECM scaffolds for 1 week respectively, and all samples were induced with hypertrophic medium for 3 weeks.…”
Section: Resultsmentioning
confidence: 99%
“…Well documented biomarkers of hypertrophy chondrocyte are type X Collagen ( COL X ), matrix metalloproteinase ( MMP‐13 ) genes, Runt domain transcription factor 2 ( RUNX2 ) and Cyclooxygenase‐2 ( COX‐2 ) are linked to chondrocyte hypertrophy as well (Frischholz, Berberich, Böck, Meffert, & Blunk, 2020; N. Liu et al., 2020; Yahara et al., 2016). The chondrocytes were treated with COL I scaffolds and dSCECM scaffolds for 1 week respectively, and all samples were induced with hypertrophic medium for 3 weeks.…”
Section: Resultsmentioning
confidence: 99%
“… Zheng et al (2020) showed that activation of AMPK/Drp1/mitochondrial fission pathway mediates chondrocyte death and migration injury ( Figure 3I ). Moreover, AMPK participated in chondrocyte dysfunction, hypertrophy, and fibrotic differentiation ( Liu N. et al, 2020 ; Liu Z. et al, 2020 ). Petursson et al (2013) and Zhou et al (2017) showed that downregulation of AMPK signaling resulted in inhibition of matrix catabolic responses in articular chondrocytes during OA development.…”
Section: Ampk In Chondrocytesmentioning
confidence: 99%